Conventional and Radiation Synthesis of Polymeric Nano- and Microgels and Their Possible Applications - J.M. Rosiak; P. Ulanski; S. Kadlubowski (Eurasian Chemico-Technological Journal, 2007)
Soft nanomaterials – polymeric nanogels and microgels – have made a fast and brilliant career, from an unwanted by-product of polymerization processes to an important and fashionable topic of interdisciplinary research in the fields of polymer chemistry and physics, materials science, pharmacy and medicine. Together with their larger analogues – macroscopic gels, most known in the form of water-swellable hydrogels – they have a broad field of actual and potential applications ranging from filler materials in coating industry to modern biomaterials.  A multitude of techniques has been described for the synthesis of polymeric nano- and microgels. Most of them can be classified in two groups. The first one are techniques based on concomitant polymerization and crosslinking (where the substrates are monomers or their mixtures), called by some authors "crosslinking polymerization". The second group are methods based on intramolecular crosslinking of macromolecules (where the starting material is not a monomer, but a polymer). The possibilities of employing macroscopic polymer gels as biomaterials, mostly in the form of hydrogels based on synthetic polymers, have been explored since 1960's, when these materials were first synthesized [1]. Since then, a number of products reached the stage of commercial application, soft contact lenses, drug delivery systems and wound dressings being the most widely known examples. Given the number of research groups involved and progress being made in this field, one may anticipate that in the future the number of hydrogel-based biomedical products on the market will be constantly increasing.